Alien-Invasion Films Imperialism, Race and Gender in the American Security State, 1950-2020 - Wildermuth, Mark E. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book studies American science fiction films depicting invasions of the USA and Earth by extra- terrestrials within the context of imperialism from 1950-2020. It shows how such films imagine America and its allies as objects of colonial control. This trope enables filmmakers to explore the ethics of American interventionism abroad either by defending the status quo or by questioning interventionism. The study shows how these films comment on American domestic hegemonic practices regarding racial or gender hierarchies, as well as hegemonic practices abroad. Beginning with the Cold War consensus in the 1950s, the study shows how hegemony at home and abroad promotes division in the culture. Mark E. Wildermuth is Dunagan Professor of English at the University of Texas Permian Basin in Odessa, Texas, USA, where he has taught since 1992. He has published articles in journals like The Journal of Popular Film and Television and Philosophy and Rhetoric. He has published 4 books: Blood in the Moonlight: Michael Mann and Information Age Cinema; Print, Chaos and Complexity: Samuel Johnson and Eighteenth-Century Media Culture; Gender, Science Fiction Television and the American Security State, 1958-Present; and Feminism and the Western in Film and Television.
Chapter 1: Introduction -- 2: An Overview of the History of American Imperialism and the American Security State -- 3: The First Post-War Security State Films, 1950-1956 -- Chapter 4: Invasion Films in the 1960's Post-Camelot Security State -- Chapter 5: Nixon, Post-Détente and Invasion Films in the 1970s -- Chapter 6: Invasion Films in the Reagan Era -- Chapter 7: Invasion Films and the 1990s Interregnum -- Chapter 8: Invasion Films After 9/11: the Bush and Obama Regimes -- Chapter 9: Invasion Films After 9/11 in the Trump Regime -- Chapter 10: Conclusions.
Keywords: Film genres; Motion pictures, American; Genre Studies; American Film and TV